Snowball Throwing: An English Learning Method to Improve Vocabulary Mastery and Psychomotor Ability - Syams Kusumaningrum; Irna Ganda Setyawati; Anam Sutopo; Koesoemo Ratih; Taha Ibrahim Ahmad Badri; Ku Ares Tawandorloh (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2020)
Vocabulary and psychomotor abilities are two important things in learning English especially for elementary school students. In mastering these two competencies we need a learning strategy that is not only able to explain but also to describe and illustrate. Snowball throwing is a learning method that uses a paper which contains a word that is shaped like a ball. This method is usually used in learning English. This research tries to find out the influence of the snowball throwing method towards students’ vocabulary mastery and psychomotor ability in learning English in the first grade of SD Islam Terpadu Sorong City. The research is quasi-experimental by using randomized pre-post control group design. The subject of this research consists of two groups; experiment and control groups have 27 students in each. There are two instruments in this research; they are the test for English vocabulary and psychomotor ability. The data are examined by using a non-parametric tests such as Mann Whitney U dan Wilcoxon signed ranks. Related to the result of the hypothesis test towards the two paired samples, we can find that the score of English vocabulary mastery (p= 0,000) and psychomotor ability (p=0,016) are significant, where the significance score of experiment group is lower than the critical limit of the research 0,05. So, we can conclude that the snowball throwing method influences significantly towards students’ vocabulary mastery and psychomotor ability at the first grade of SD Islam Terpadu Sorong City. This research shows that snowball throwing method can be used to improve students’ vocabulary mastery and psychomotoric ability in English subject.